Compensation of temporal averaging bias in solar irradiance data. Issue 10 (8th June 2017) - Gibson, Keith; Cole, Ian R.; Goss, Brian; Betts, Thomas R.; Gottschalg, Ralph
Abstract : Solar irradiance data is used for the prediction of solar energy system performance but is presently a significant source of uncertainty in energy yield estimation. This also directly affects the expected revenue, so the irradiance uncertainty contributes to project risk and therefore the cost of finance. In this study, the combined impact of temporal averaging, component deconstruction and plane translation mechanisms on uncertainty is analysed. A new method to redistribute (industry standard) hourly averaged data is proposed. This clearness index redistribution method is based on the statistical redistribution of clearness index values and largely corrects the bias error introduced by temporal averaging. Parameters for the redistribution model were derived using irradiance data measured at high temporal resolution by CREST, Loughborough University, over a 5‐year period. The root mean square error of example net annual (2014) diffuse, beam and global yield of hourly averaged data were reduced from ∼15 to 1, 14 to 3 and 4 to 1%, respectively.